The effect of MgO/TiO2 on structural and crystallization behavior of near invert phosphate‐based glasses. Issue 3 (7th June 2019) - Islam, Md Towhidul; Sharmin, Nusrat; Rance, Graham A.; Titman, Jeremy J.; Parsons, Andrew J.; Hossain, Kazi M. Zakir; Ahmed, Ifty
Abstract: Varying formulations in the glass system of 40P2 O5 ─(24 − x )MgO─(16 + x )CaO─(20 − y )Na2 O─ y TiO2 (where 0 ≤ x ≤ 22 and y = 0 or 1) were prepared via melt‐quenching. The structure of the glasses was confirmed by X‐ray diffraction (XRD), Fourier transform infrared (FTIR), micro Raman and solid‐state nuclear magnetic resonance (NMR) spectroscopies. The thermal properties and the activation energy of crystallization ( E c ) were measured using thermal analysis and the Kissinger equation, respectively. The glass forming ability of the formulations investigated was seen to decrease with reducing MgO content down to 8 mol% and the glass stability region also decreased from 106 to 90°C with decreasing MgO content. The activation energy of crystallization ( E c ) values also decreased from 248 (for 24 mol% MgO glass) to 229 kJ/mol (for the 8 mol% MgO content) with the replacement of MgO by CaO for glasses with no TiO2 . The formulations containing less than 8 mol% MgO without TiO2 showed a strong tendency toward crystallization. However, the addition of 1 mol% TiO2 in place of Na2 O for these glasses with less than 8 mol% MgO content, inhibited their crystallization tendency. Glasses containing 8 mol% MgO with 1 mol% TiO2 revealed a 12°C higher glass transition temperature, a 14°C increase in glass stability against crystallization and a 38 kJ/mol increase in E c in comparison to their non TiO2 containing counterpart. NMR spectroscopy revealed that all of the formulations contained almost equal percentages of Q 1 and Q 2 species. However, FTIR and Raman spectroscopies showed that the local structure of the glasses had been altered with addition of 1 mol% TiO2, which acted as a network modifier, impeding crystallization by increasing the cross‐linking between phosphate chains and consequently leading to increased E c as well as their glass forming ability.